Figurative approach to the quantitative evaluation of the value of information - Zaiats, V.M.; Zaiats, M.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
On the basis of the theory of pattern recognition, a new approach is proposed that allows one to quantify the value of information. Different approaches to the determination and calculation of basic concepts of information theory are considered, in particular, the amount of information and evaluation of its value, based on statistical considerations (the classical approach), the theory of algorithms (algorithmic approach), and the theory of pattern recognition (figurative approach). Their analysis is carried out, and the limits of their use and the fields of effective application are marked.